On-chip High-Voltage Generator Design Design Methodology for Charge Pumps - Tanzawa, Toru.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides various design techniques for switched-capacitor on-chip high-voltage generators, including charge pump circuits, regulators, level shifters, references, and oscillators.  Readers will see these techniques applied to system design in order to address the challenge of how the on-chip high-voltage generator is designed for Flash memories, LCD drivers, and other semiconductor devices to optimize the entire circuit area and power efficiency with a low voltage supply, while minimizing the cost.  This new edition includes a variety of useful updates, including coverage of power efficiency and comprehensive optimization methodologies for DC-DC voltage multipliers, modeling of extremely low voltage Dickson charge pumps, and modeling and optimum design of AC-DC switched-capacitor multipliers for energy harvesting and power transfer for RFID.
System Overview and Key Design Considerations -- Switched Capacitor Voltage Multipliers -- Design of DC-DC Dickson Charge Pump -- Design of AC-DC Charge Pump -- Charge Pump State of the Art -- Pump Control Circuits -- System Design.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation